The influence of stacking fault energy on the mechanical properties of nanostructured Cu and Cu–Al alloys processed by high-pressure torsion - An, X.H.; Lin, Q.Y.; Wu, S.D.; Zhang, Z.F.; Figueiredo, R.B.; Gao, N.; Langdon, T.G. (Scripta materialia, 2011)
► Nanostructured Cu and Cu-Al alloys were prepared by high-pressure torsion. ► The strengths increase with decreasing stacking fault energy (SFE). ► The strength of NS alloys with low Al content is sensitive to the loading conditions. ► The ductility also increases except at the lowest SFE where the ductility decreased. ► There is an optimal SFE for ductility in the NS alloys processed by various methods. Nanostructured (NS) Cu and Cu–Al alloys were processed by high-pressure torsion to systematically investigate the influence of stacking fault energy (SFE) on the mechanical properties. It is shown that the strength increases with decreasing SFE and the strength of NS materials with lower Al content is especially sensitive to the characteristics of the processing conditions. The uniform elongation generally increases with decreasing SFE, but this trend is reversed at the smallest grain size of ∼30 nm.